Memahami Popularitas Perang Takjil di Kalangan Komunitas Non-Muslim: Sebuah Analisis Sosial Budaya - Nada, Vela Qotrun; Ma'arif, Syamsul (Proceedings of International Conference on Muslim Society and Thought, 2024)
One of tradition that very attached to the month of Ramadan is ngabuburit. The latest crowded on social media and being discussed by many people is the takjil war which is not only participated by Muslims but also by non-Muslims, showing the diversity and harmony between people in Indonesia. To study this phenomenon, a qualitative research type with a phenomenological approach is used. Data collection techniques include observation, interviews, and documentation. Observation data sources are obtained through the direct phenomenon of takjil wars on social media, then interviews are obtained directly from the takjil war perpetrators. The results of this study show that the popularity of takjil war among non-Muslims reflects the spirit of inclusiveness and social solidarity in a multicultural society. It shows that activities originating from a particular culture or religion can be a point of unity and collaboration across cultures.